Metabolic syndrome, circulating RBP4, testosterone, and SHBG predict weight regain at 6 months after weight loss in men. - Wang, P; Menheere, P; Astrup, A; Andersen, MR; Baak, v; Larsen, T; Jebb, S; Kafatos, A; Pfeiffer, A; Martinez, J; Handjieva-Darlenska, T; Hlavaty, P; et al. (2013)
OBJECTIVE: Weight loss helps reduce the symptoms of the metabolic syndrome (MetS) in the obese, but weight regain after active weight loss is common. The changes and predictive role of circulating adipokines and sex hormones for weight regain in men during dietary intervention, and also the effect of basal MetS status on weight regain, were investigated. DESIGN AND METHODS: Twenty-four men who continued to lose weight (WL) and 24 men who regained weight (WR) during the 6-month follow-up period after weight loss were selected from the Diogenes Study. Their circulating concentrations of leptin, adiponectin, retinol-binding protein 4 (RBP4), luteinizing hormone, prolactin, progesterone, total and free testosterone, and sex hormone-binding globulin (SHBG) were measured at baseline, after 8-week low-calorie diet-induced active weight loss, and after a subsequent 26-week ad libitum weight maintenance diet, and analyzed together with anthropometrical and physiological parameters. RESULTS: Overweight and obese men with MetS at baseline had higher risk to regain weight (odds ratio = 2.8, P = 0.015). High baseline RBP4, low total testosterone, and low SHBG are predictors of weight loss regain (different between WR and WL with P = 0.001, 0.038, and 0.044, respectively). CONCLUSIONS: These variables may play roles in the link between MetS and weight loss regain.